223 Functional neurological symptom disorder & autistic spectrum disorders: a litera- ture review of co-incidence and shared mechanisms. Issue 6 (27th May 2022) - Roelofs, Jacob; Petrochilos, Panayiota; Selai, Caroline
Abstract : Functional Neurological Symptom Disorder (FNSD) and Autistic Spectrum Disorders (ASD) are both complex and incompletely understood conditions. This review investigates the literature for evidence of associa- tion between them. A literature search produced nine Results three case reports and six epidemiological studies. The case reports describe the conditions co-occurring, providing anecdotal evidence of an association. Nimmo- Smith and Lever reported 2.5-fold and three-fold higher prevalence of 'somatoform disorders' in ASD samples compared to the general population (Lever 2016; Nimmo-Smith 2020). Jester and Schendel published studies which both suggest higher rates of functional symptoms in ASD patients, are limited by methodological issues (Jester 2016; Schendel 2019). Only the study by Roy reported no difference; 8% prevalence compared to 7.5% (Roy 2015). McWilliams et al reported a case series showing a much higher rate of ASDs in 59 young people with non-epileptic seizures; 16.9%, compared to 1.3–1.5% in the general population (McWilliam 2019). The range of terminology and methodology used makes integrating the results difficult, but overall there is evidence of an association between ASD and FNSD. Potential mechanisms linking the two such as emotional dysregulation and alexithymia are highlighted, as well as brain regions including the amygdala and anterior cingulate cortex (ACC). jacob.john.roelofs@gmail.com